1987
DOI: 10.1002/tera.1420350311
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and noncardiac malformations: Observations in a population‐based study

Abstract: A regional case-control study of congenital cardiovascular malformations (CCVMs) searches for all live-born infants in the community in whom the cardiac diagnosis has been confirmed by echocardiography, cardiac catheterization, surgery, or autopsy. Their families are studied in comparison to those of a representative sample of resident live-born infants. Detailed descriptions of noncardiac abnormalities are obtained from physician reports and maternal interviews expanded by medical record and death certificate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
1
3

Year Published

1989
1989
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(43 citation statements)
references
References 11 publications
5
32
1
3
Order By: Relevance
“…44 Congenital cardiac defects also occur in association with congenital syndromes and extracardiac anomalies more frequently than would be expected by chance alone. 200,201 There is a higher frequency of cardiac defects in the relatives of children born with cardiac defects 202 and the recurrence risk in offspring of affected parents suggests both single and multiple gene inheritance is occurring, particularly for some lesions. 42 Certain factors are associated with worse outcomes from congenital heart defects, including the type and complexity of the malformation, associated extracardiac anomalies and congestive heart failure.…”
Section: Antenatal and Perinatal Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Congenital cardiac defects also occur in association with congenital syndromes and extracardiac anomalies more frequently than would be expected by chance alone. 200,201 There is a higher frequency of cardiac defects in the relatives of children born with cardiac defects 202 and the recurrence risk in offspring of affected parents suggests both single and multiple gene inheritance is occurring, particularly for some lesions. 42 Certain factors are associated with worse outcomes from congenital heart defects, including the type and complexity of the malformation, associated extracardiac anomalies and congestive heart failure.…”
Section: Antenatal and Perinatal Factorsmentioning
confidence: 99%
“…The Baltimore-Washington Infant Study identified the extracardiac malformations most commonly associated with congenital heart defects (gastrointestinal, genitourinary and ophthalmic), but if these were unlikely to be identified on the first day of life, they were not considered to be reasons for exclusion from screening. 200 We used data from a UK study of cardiac defects associated with gastrointestinal defects at birth to determine which gastrointestinal defects should be used as criteria for exclusion from routine cardiac screening. 75 We further contacted specialists in the field to enquire about current practice in investigating the cardiac status of children with gastrointestinal defects and to what extent these were identifiable on the first day of life (Spitz L, Institute of Child Health and Great Ormond Street Hospital, London: personal communication, 2002).…”
Section: Newborns With Extracardiac Defects Associated With Congenitamentioning
confidence: 99%
“…Pradat retrospectively observed the data of children with major CHD in Sweden. 7 Extracardiac malformation was identified in 25.7% patients after excluding 15% of the children with chromosomal anomalies. Bosi et al retrospectively evaluated CHD in Italy and found 24% of these patients had extracardiac malformations.…”
Section: Discussionmentioning
confidence: 99%
“…Ferencz et al conducted study of CHD among live births in the US. 7 Extracardiac anomalies were observed among 26.8% of the individuals with CHD, 93% of which were associated with chromosomal anomalies or other syndromes. Central nervous system malformations, gastrointestinal and urinary tract defects were more frequent among the patients with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…In a literature review, only two publications in English language were found with similar goal to our study, that was to evaluate presence of abdominal malformations in patients with CHD through AUS 9,10 . In contrast, our study is unique in that all CHD patients underwent AUS, high resolution karyotype and FISH for detection of microdeletion 22q11.2, and all were examined by a clinical geneticist 7,[8][9][10][18][19][20][21][22][23][24][25][26][27][28][29][30] .…”
Section: Discussionmentioning
confidence: 99%